Interpretations of sumbanese Ikat by instagram influencers - Monica Hartanti; Yunita Setyoningrum; Yudita Royandi; Aulia, W. A (Penerbit Universiti Kebangsaan Malaysia, 2023)
Ikat Sumba is considered a noble Indonesian traditional textile art because the process of making it is very long, and the motifs are very distinctive with local geographical indications. Influencers create various activities with Sumba cloth by posting feeds on Instagram social media. The impression of fashion affairs on Instagram attracts influencers, brand products, and Instagram users. This research analyses six digital influencers on Instagram as actors who engage with Ikat Sumba. Digital influencers with different backgrounds and characters certainly bring different points of view through pictures and captions on their Instagram accounts about these cultural artifacts. Instagram feeds and captions from Ikat Sumba influencers who produce texts, distribute, and respond will create different interpretations of Ikat Sumba. This research uses descriptive qualitative methods and was analysed in more depth using Norman Fairclough's discourse analysis and supported data by network analysis using ACNA. The findings in this research reveal that Ikat Sumba is a traditional Indonesian fabric art that is not only valuable but also represents love, clothing, and the local community in Indonesia. The interpretation to market the product should present the precious values of Sumbanese ikat as a noble craft that explores narratives of love, clothes, and people instead of showing specific physical details of the textile. Social media influencers influence the creation of interpretations of traditional works of art. This could be the future of Sumba Weaving related contents in Instagram with an informative and attractive appearance to increase the value of Sumba Weaving so that it is more widely known and influence marketing efforts.